High diversity of fish ectoparasitic monogeneans (Dactylogyrus) in the Iberian Peninsula: a case of adaptive radiation?. Issue 4 (22nd April 2020) - Benovics, Michal; Desdevises, Yves; Šanda, Radek; Vukić, Jasna; Scheifler, Mathilde; Doadrio, Ignacio; Sousa-Santos, Carla; Šimková, Andrea
Abstract: The epicontinental fauna of the Iberian Peninsula is strongly influenced by its geographical history. As the possibilities for dispersion of organisms into and from this region were (and still are) limited, the local fauna consists almost exclusively of endemic species. Almost all Iberian freshwater fishes of the families Leuciscidae and Cyprinidae are endemic and on-going research on these taxa continually uncovers new species. Nevertheless, information on their host-specific parasites remains scarce. In this study, we investigate the diversity and phylogenetic relationships in monogeneans of the genus Dactylogyrus (gill ectoparasites specific to cyprinoid fish) in the Iberian Peninsula. Twenty-two species were collected and identified from 19 host species belonging to Cyprinidae and Leuciscidae. A high degree of endemism was observed, with 21 Dactylogyrus species reported from Iberia only and a single species, D. borealis, also reported from other European regions. Phylogenetic analysis split the endemic Iberian Dactylogyrus into two well-supported clades, the first encompassing Dactylogyrus parasitizing endemic Luciobarbus spp. only, and the second including all Dactylogyrus species of endemic leuciscids and four species of endemic cyprinids. Species delimitation analysis suggests a remarkable diversity and existence of a multitude of cryptic Dactylogyrus species parasitizing endemic leuciscids ( Squalius spp. and representatives of Chondrostoma s.l. ). These results suggest a rapid adaptive radiation of Dactylogyrus in this geographically isolated region, closely associated with their cyprinoid hosts. Moreover, phylogenetic analysis supports that Dactylogyrus parasites colonized the Iberian Peninsula through multiple dispersion events.